Inflammasome activation and accelerated immune aging in autoimmune disorders - Mittal, Rahul; Saavedra, Danay; Mittal, Mannat; Lemos, Joana R. N.; Hirani, Khemraj (Frontiers in Aging, 2025)
Autoimmune diseases, particularly those with early onset such as systemic lupus erythematosus, juvenile idiopathic arthritis, and type 1 diabetes, are paradoxically characterized by molecular and cellular features typically associated with aging. These include telomere shortening, mitochondrial dysfunction, epigenetic alterations, and skewed immune cell phenotypes, which are considered hallmarks of immunosenescence. This perspective explores the hypothesis that aberrant inflammasome activation, particularly of the NLRP3 complex, serves as a key upstream driver of premature immune aging in autoimmunity. We examine how chronic inflammasome signaling induces senescence through pro-inflammatory cytokine production and oxidative stress, reinforces the senescence-associated secretory phenotype (SASP), and perpetuates immune dysregulation. By reframing autoimmunity as a disorder of accelerated immune aging, we highlight emerging opportunities for therapeutic intervention using senolytics, inflammasome inhibitors, and lifestyle modifications. In addition, incorporating biomarkers of immune aging into clinical assessment may enable precision immunogerontology, particularly in pediatric populations where biological and chronological age may be dissociated. Elucidating the relationship between inflammasome signaling and immune senescence provides a critical framework for understanding autoimmune pathogenesis and for developing interventions that modify disease course by targeting age-associated mechanisms.